The Influence of MUI Halal Certificates on Buying Interest and Consumer Confidence - Harahap, Shelvi Fadillah; Rokan, Mustapa Khamal; Syarbaini, Ahmad Muhaisin B (Image : Jurnal Riset Manajemen, 2024)
This study aims to determine the effect of halal certificates on buying interest and consumer confidence in mixue. The method used by this research is quantitative method. The data source in this study comes from primary data, namely the results of distributing questionnaires / surveys through google form media.  The population of this study were FEBI UINSU students totaling 4,490 people. The sampling method uses simple random sampling technique, where the sample is drawn randomly in the population. The number of samples in this study were 100 respondents using the Slovin formula. Data analysis using SPSS 25 for windows software with instrument test, validity test, reliability test, normality test, linearity analysis, and significance test (t test). The results showed that halal certificates had a positive and significant effect on buying interest as indicated and the halal certificate variable has a positive and significant effect on consumer confidence.